Local elections 1979 - Voters' study - Brantgärde, Lennart; Magnusson, Håkan; Westerståhl, Jörgen; Strömberg, Lars; Gidlund, Janerik; Wallin, Gunnar; Johansson, Leif; Törnqvist, Gunnar; Olander, Lars-Olof; Widberg, Jan (University of Gothenburg, 1982)
The second project started as a result of a decision of the Swedish Parliament taken in December 1978. The research program was designed by a government commission, the Commission on Local Democracy, in collaborations with members of the previous Local Government Research Group. The purpose of this project was to evaluate the reapportionment reform which had been implemented five years earlier, to some extent in relation to research findings of the previous project. In five communes, which were to be the object of more intensive studies, the interview sample comprised 300 persons per commune. In the other 45 communes the sample comprised 40 persons per commune. The interview scheme contained questions about the respondent´s opinion of the local authorities achievements in different issues, such as child care, care of the aged, schools, and housing. A question concerning the priorities of activities covered 14 fields of service and within each field the respondent were asked whether the service was good as it was, needed to be increased, or could be reduced. Other questions dealt with the respondent´s contacts with local administrative authorities in specific matters. These were followed by questions on political activity, i.e. activity which concerned communal decisions and plans, via political parties, via local government officers or via manifestations and action groups. A number of questions measured the respondent´s knowledge of local election issues, names of the candidates, the political majority situation in the communes, and the personal acquaintance with local politicians. The intensive study of five communes, Grästorp, Kävlinge, Linköping, Luleå, and Sjöbo contained the same questions as the Voters´ study, but it also included a number of questions about specific local issues and local service.

The Voters' study include respondents from all 50 municipalities.

The second project started as a result of a decision of the Swedish Parliament taken in December 1978. The research program was designed by a government commission, the Commission on Local Democracy, in collaborations with members of the previous Local Government Research Group. The purpose of this project was to evaluate the reapportionment reform which had been implemented five years earlier, to some extent in relation to research findings of the previous project. In five communes, which were to be the object of more intensive studies, the interview sample comprised 300 persons per commune. In the other 45 communes the sample comprised 40 persons per commune. The interview scheme contained questions about the respondent´s opinion of the local authorities achievements in different issues, such as child care, care of the aged, schools, and housing. A question concerning the priorities of activities covered 14 fields of service and within each field the respondent were asked whether the service was good as it was, needed to be increased, or could be reduced. Other questions dealt with the respondent´s contacts with local administrative authorities in specific matters. These were followed by questions on political activity, i.e. activity which concerned communal decisions and plans, via political parties, via local government officers or via manifestations and action groups. A number of questions measured the respondent´s knowledge of local election issues, names of the candidates, the political majority situation in the communes, and the personal acquaintance with local politicians. The intensive study of five communes, Grästorp, Kävlinge, Linköping, Luleå, and Sjöbo contained the same questions as the Voters´ study, but it also included a number of questions about specific local issues and local service.

Medborgarundersökningen omfattar respondenter från samtliga 50 kommuner.
Kommunala valrörelser 1979 - Medborgarundersökningen
Keywords: elections; val; housing; boende; mass media; massmedia; participation; deltagande; politics; politik; public sector; offentlig sektor; mass media exposure; massmediaexponering; residential mobility; flyttningsbenägenhet; local government policy; kommunalpolitik; local government elections; kommunalval; voting intention; röstavsikt; child care; barnomsorg; citizenship skills; medborgerliga färdigheter; voting; röstning; political interest; politiskt intresse; local government services; kommunal service; membership; medlemskap; information sources; informationskällor; news; nyheter; political influence; medborgarinflytande; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; political parties; politiska partier; schools; skolor; electoral issues; valfrågor; clubs; föreningar; commuting; pendling; lobbying; politisk påverkan; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Political ideology; Politisk ideologi; Government, political systems and organisations; Regering, politiska system och organisationer; Community, urban and rural life; Lokalsamhälle, stads- och landsbygdsliv; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap